2021
DOI: 10.13102/sociobiology.v68i1.6021
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the small hive beetle (Aethina tumida) in Melipona rufiventris colonies in Brazil

Abstract: Several traits make stingless bees attractive to parasites of honey bee colonies. The small hive beetle (SHB) Aethina tumida, a honey bee colony scavenger/parasite native to sub-Saharan Africa, where is considered only a minor pest, is now present on almost all continents, including the Latin America region in South America. SHB has been recorded in Brazil since 2016 in Africanized honey bees and generaly the beetle does not seem cause negative impacts. European honey bees, on the other hand, suffer considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
1
0
4
Order By: Relevance
“…Como se indicó, A. tumida puede infestar abejas nativas sin aguijón (Loriga-Peña et al, 2014;Pereira et al, 2021) y abejorros (Hoffmann et al, 2008), tanto en campo, como en condiciones de invernadero, como se ha reportado en Norteamérica (Spiewok & Neumann, 2006).…”
Section: Reportes Sobre La Presencia Del Pequeño Escarabajo De La Col...unclassified
See 3 more Smart Citations
“…Como se indicó, A. tumida puede infestar abejas nativas sin aguijón (Loriga-Peña et al, 2014;Pereira et al, 2021) y abejorros (Hoffmann et al, 2008), tanto en campo, como en condiciones de invernadero, como se ha reportado en Norteamérica (Spiewok & Neumann, 2006).…”
Section: Reportes Sobre La Presencia Del Pequeño Escarabajo De La Col...unclassified
“…Se indica su presencia en colonias de Melipona beecheii en Cuba (Loriga-Peña et al, 2014), Dactylurina staudingerii en el oeste de África (Mutsaers, 2006), Trigona carbonaria (Greco et al, 2010) y Austroplebeia australis en Australia (Halcroft et al, 2011). Asi como, en colonias de Melipona rufiventris en Brasil (Pereira et al, 2021) y en nidos de Plebeia frontalis en México (Toledo-Hernández et al, 2021).…”
Section: Reportes Sobre La Presencia Del Pequeño Escarabajo De La Col...unclassified
See 2 more Smart Citations
“…In addition to the considerable damage SHB can cause to apiculture in the invasive ranges (Delaplane, 1998), research revealed the generalist nature of SHB. Indeed, SHB can infest nests of other social and solitary bee species (bumblebees: Ambrose et al, 2000;Spiewok & Neumann, 2006;reviewed by Neumann et al, 2016;solitary bees: Gonthier et al, 2019;stingless bees: Nacko et al, 2020;Pereira et al, 2021). They can also feed on flowers (Gonthier et al, 2019) and can succesfully reproduce on fruits and other foods, including rotten meat (Buchholz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%